Comparison of High Hip Center versus Anatomical Reconstruction Technique in Crowe Types II and III Developmental Dysplasia of the Hip: a Retrospective Clinical Study - Demirel, M; Kendirci, A S; Saglam, Y; Ergin, O N; Sen, C; Öztürk, I (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
PURPOSE OF THE STUDY The literature is conflicting as to whether the high hip center (HHC) reconstruction in total hip arthroplasty (THA) is an ideal option for patients with severe developmental dysplasia of the hip (DDH). This study aimed to compare the mid-term functional and radiographic outcomes of THA using HHC versus anatomical hip center (AHC) technique in Crowe types II and III DDH. Our hypothesis was that there may be no differences in terms of functional and radiographic outcomes between patients who underwent THA using HHC or AHC. MATERIAL AND METHODS Fifty-seven patients who underwent a primary THA due to Crowe type-II or type-III DDH were retrospectively reviewed and included. Patients were divided into two groups as per the hip center reconstruction: Group A (AHC technique) and group H (HHC technique). A cementless cup was inserted in 25 hips (19 female, 6 male; mean age = 51 years, age range = 28-67)) at near-AHC in group A and 32 hips (22 female, 10 male; mean age = 53 years, age range = 29-68) at HHC position in group H. To assess clinical status, the Harris Hip Score (HHS) was used at the final follow-up. In radiographical assessment, component loosening and osseointegration of the acetabular cup were examined on follow-up radiographs. Complications were also recorded. RESULTS The mean follow-up was 41 months (range, 25-84) in group A and 40 months (range, 24-86) in group H. The mean HHS was 83 (range, 74-91) in group A and 83.6 (range, 73-94) in group H (p = 0.741). Osteolysis was determined in three patients from each group. The other 51 cups demonstrated a minimum of one radiographic sign of osseointegration. Although the overall complication rate was higher in group A (64%) than in group H (46%), this difference reached no statistical significance (p = 0.11). CONCLUSIONS The HHC technique using cementless acetabular fixation seems to be a valuable alternative option to AHC technique in cases of Crowe types II and III DDH. Key words: High hip center; anatomical hip center; center of rotation; total hip arthroplasty; dysplastic hip; developmental dysplasia of the hip; Crowe type II; Crowe Type III.
Keywords: dospělí; vývojová kyčelní dysplazie; Female; kyčelní protézy; Adult; výsledek terapie; ženské pohlaví; vývojová dysplazie kyčelního kloubu; lidé; Treatment Outcome; následné studie; Developmental Dysplasia of the Hip; retrospektivní studie; Follow-Up Studies; Male; Aged; náhrada kyčelního kloubu; lidé středního věku; Arthroplasty, Replacement, Hip; senioři; mužské pohlaví; Retrospective Studies; Hip Dislocation, Congenital; Middle Aged; Hip Prosthesis; Humans